OPTIMISING THE RECRUITMENT OF TEACHERS FOR SCARCE SKILLS SUBJECTS IN RURAL SECONDARY SCHOOLS: A STUDY OF PRACTICES IN AFRICAN COUNTRIES - Matodzi Grace Muremela,; Azwidohwi Phillip Kutame,; Ingrid Sibongile Kapueja,; Oluwatoyin Ayodele Ajani, (International Journal of Innovative Technologies in Social Science, 2024)
This scoping review investigates strategies for optimising the recruitment of teachers specialising in scarce skills subjects in rural secondary schools across African countries. Using human capital theory as the theoretical framework, the study explores how various recruitment practices impact the availability and effectiveness of qualified teachers in these critical areas. A total of 344 articles were initially accessed through Scopus and Google Scholar, of which 57 peer-reviewed articles published in English were selected for thematic analysis. The review reveals several key themes related to recruitment practices, including the influence of financial incentives, professional development opportunities, and community engagement. It also highlights the significant barriers faced in rural settings, such as infrastructural deficiencies, low attractiveness of teaching careers in these areas, and challenges related to retention of teachers. The findings underscore the necessity for targeted policies that address these specific challenges and enhance the appeal of teaching in rural schools. Recommendations include increasing investment in teacher training programmes, providing competitive incentives, and fostering partnerships between educational institutions and local communities to support teacher recruitment and retention.